The Candida albicans Dse1 Protein Is Essential and Plays a Role in Cell Wall Rigidity, Biofilm Formation, and Virulence - Daher, Jalil Y.; Koussa, Joseph; Younes, Samer; Khalaf, Roy A. (Interdisciplinary Perspectives on Infectious Diseases, 2011)
The fungal pathogen Candida albicans is one of the leading causative agents of death in immunocompromised individuals. It harbors an arsenal of cell wall anchored factors that are implicated in virulence such as filamentation inducing factors, adhesins, lipases, proteases, and superoxide dismutases. Dse1 is a cell wall protein involved in cell wall metabolism. The purpose of this study is to characterize the role Dse1 plays in virulence. Dse1 appears to be an essential gene as no homozygous null mutant was possible. The heterozygote mutant exhibited increased susceptibility to calcofluor white, a cell wall disrupting agent, with a subsequent reduction in cell wall chitin content, decreased oxidative stress tolerance, a 30% reduction in biofilm formation, and a delay in adhesion that was mirrored by a reduction in virulence in a mouse model of infection. Dse1 thus appears to be an important protein involved in cell wall integrity and rigidity.